Youth Cannabis use and Legalization in Canada – Reconsidering the Fears, Myths and Facts Three Years In - Haines-Saah, Rebecca J (J Can Acad Child Adolesc Psychiatry, 2021)
Canada legalized and regulated non-medical cannabis in October 2018, and in the lead up to this policy change much debate was generated around the Federal Government’s stated objective of “keeping cannabis out of the hands of children and youth”. As Canada moved through the process of passing Bill C-45 (the Cannabis Act), a contentious issue was whether the ‘public health approach’ to legalization with strict regulation guiding Federal policy would protect young people from accessing cannabis and from the potential harms of use. Now that we are several years post-legalization of cannabis, in this brief commentary we reconsider the arguments made about the potential consequences of legalization for youth, centered on three key concerns: that prevalence would significantly increase, that there would be greater incidence of harms to youth brain development, and that there would be increased presentations of severe mental illnesses associated with cannabis use. We also consider how focusing narrowly on clinical outcomes has neglected the association between criminalization and social inequities, where the burdens are disproportionate for marginalized and racialized youth.